Dependence of cardio-respiratory system adaptation reactions of athletes to endurance training on complex of gene polymorphisms - Drozdovska, S.; Lysenko, O.; Dosenko, V.; Ilyin, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The adaptation of an athlete to systematic physical exercise has been shown to depend on an individuals inherited properties (Bouchard et al., 1999). These properties are determined by a combination of great many genes polymorphisms (Bray et al., 2009; Timmons et al., 2010). The aim of our study was to investigate the dependence of the aerobic capacity parameters in sport on the gene polymorphisms. Methods: Two hundred and ninety six athletes participated in the study of genotype features of the athletes including: 109 athletes specializing in the speed and strength sports, 103 athletes specializing in the endurance sports, and 93 volunteers which are not involved into sport. The S-786 --> C polymorphism of the promoter of eNOS gene as well as I/D polymorphism of ACE gene, Pro/Ala polymorphism of PPARG gene, G/C polymorphism of PPARA gene, Pro582Ser polymorphism of HIF1a gene, and Ala203Pro polymorphism of PPARGC1B gene were identified using the method of PCR. Adaptation to exercise was assessed using the gas analysis which was carried out by an automatic gas analyzer of the Meta Max. Stress tests were conducted using the ergometer and treadmill. Results: The impact of 6 polymorphisms on the aerobic performance level was analyzed. Cumulative impact of these polymorphisms in the combination with the individual parameters (gender; qualification; kind of sport) stipulates 71% of dispersion of VO2max value. The most stable parameters of the cardio-respiratory system reactions of the athletes in the repeated testing included: HRmax (V=1,5%), VCO2/VO2, (V=5,5%), VO2max/kg (V=5,7%), VO2max (V=5,8%), HRTh (V=5,8%), Wmax and Wmax/kg (V=5,9%), VEmax and VEmax/kg (V=7,4%), EQO2 (V=7,6%), fTmax (V=7,9%). ACE gene polymorphism has a definite effect on EQO2 (p=0,020), HRmax (p=0,029). PPARA gene polymorphism has a definite effect both on WTh (p=0.04) and WTh/kg (p=0,009). eNOS gene polymorphism has an effect on EQO2 (p=0,046). Discussion: The analysis of the obtained results has shown both single and combined effect of the gene polymorphisms on the aerobic capacity in the sports with the prevailing development of endurance. Though many studies demonstrated the exceptional significance of the maximal oxygen uptake to achieve the high sport results in the endurance sports, the necessity of VO2max high level is overestimated. Competitive activity has different requirements to the level and ratio of the factors in the functional fitness structure in the different sports. Each sport should have its own criteria of the aerobic capacity evaluation. It is necessary to focus on the sport-specific molecular-genetic markers.